PERAN TIM PENGAWALAN, PENGAMANAN PEMERINTAH DAN PEMBANGUNAN DAERAH (TP4D) KEJARI PALOPO DALAM PENCEGAHAN TINDAK PIDANA KORUPSI - Moh. Rizal Mannaba (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2018)
The purpose of this study was (1) to find out and analyze the effectiveness of the role of the escort team, government security and regional development (TP4D) at Palopo in preventing corruption, (2). Knowing and analyzing the factors that influence the implementation of the role of the Guardian Team, Government and Regional Development (TP4D) at Palopo in preventing corruption. The research conducted by the author is a type of descriptive research with a juridicalempirical approach is research that examines positive legal rules in order to get answers to existing problems by linking to facts or phenomena about the role of TP4D Palopo in preventing corruption. Research Results show that The implementation of Attorney Palopo's TP4D duties in the prevention of corruption has been carried out effectively, including: escorting and safeguarding the course of government and development through preventive efforts; provide legal assistance in each stage of the development program; coordinate with the Internal Government Supervisory Apparatus (APIP) to prevent irregularities; monitoring and evaluating the implementation of work and development programs.